Monopoly, Non-Linear Pricing and Imperfect Information: The Insurance Market - Stiglitz, Joseph E. (Review of Economic Studies, 1977)
Stiglitz establishes the relationship between monopoly, non-linear pricing, and imperfect information in the insurance market.